2013
DOI: 10.1177/0954405413506195
|View full text |Cite
|
Sign up to set email alerts
|

Rotary ultrasonic machining of optical K9 glass using compressed air as coolant: A feasibility study

Abstract: Optical K9 glass has been used in a variety of applications, including optics, electronics, thermodynamics, and fluidics. It has been regarded as a difficult-to-cut material because of its superior mechanical properties. Rotary ultrasonic machining using cutting fluid has been used successfully to machine many different types of brittle materials, such as ceramics, sapphire, and optical K9 glass. Dry machining has been successfully employed in the machining of some materials. However, there are no reported inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 32 publications
2
62
1
Order By: Relevance
“…K9 glass has been used as a representative functional material in many applications, such as optics, electronics, thermodynamics, fluidics, and so on [2]. K9 glass is regarded as a difficult-to-machine material due to its mechanical properties, such as high hardness, high strength, and low fracture toughness [3]. Other material properties that give K9 glass a broad application include its low density, high thermal resistance, and good resistance to corrosion and wear.…”
Section: K9 Glassmentioning
confidence: 99%
See 4 more Smart Citations
“…K9 glass has been used as a representative functional material in many applications, such as optics, electronics, thermodynamics, fluidics, and so on [2]. K9 glass is regarded as a difficult-to-machine material due to its mechanical properties, such as high hardness, high strength, and low fracture toughness [3]. Other material properties that give K9 glass a broad application include its low density, high thermal resistance, and good resistance to corrosion and wear.…”
Section: K9 Glassmentioning
confidence: 99%
“…Matsumura et al reported the use of abrasive water jet to make grooves of 20-100 µm wide on glass [6]. Rotary ultrasonic machining (RUM) has also been applied to K9 glass machining [3,[7][8][9]. Paragraphs that follow will give more details to introduce the RUM process and the state-of-the-art of its application to K9 glass machining.…”
Section: K9 Glassmentioning
confidence: 99%
See 3 more Smart Citations